Nuevos registros de macromicetos para Colombia (2016)
ABSTRACT: We present the results of a study carried out in the tropical dry forest at the Meteorological Station of CARSUCRE, in the municipality of Colosó, Sucre (Colombia). We used line transects of 100 m in length, along the creek Sereno and on the top of the hills; we sampled along such transects from February to August and in November 2011. A total of 182 specimens were collected, belonging to the phyla Ascomycota (4 genera and 11 species) and Basidiomycota (31 genera and 59 species). Moreover, we report 39 new records for Sucre and seven new records for Colombia. Finally, this work is a pioneering study for the Department of Sucre, because there is no information about wild fungi in dry tropical forest (Bs-T).